Analysis of Sharia-Based Financial Reports in Improving Company Performance (Case Study on Sharia Indonesian Rakyat Bank Which Listed on Indonesia Stock Exchange) - Nijatul Azira; Riski Hermawan; Ahmad Fauzul Hakim Hasibuan; Siti Zuraida (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The author conducted this research at PT Bank Rakyat Indonesia Syariah Tbk. In this study the aim was to determine the performance of sharia-based finance in improving company performance (a case study on Islamic Indonesian people's banks listed on the Indonesian stock exchange , the type of data used is secondary data , data collection techniques used are data analysis techniques and quantitative descriptive methods.